2014
DOI: 10.1016/j.neuron.2014.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Neural Mechanisms of Decision Making and Their Competition under Changing Risk Pressure

Abstract: SummarySometimes when a choice is made, the outcome is not guaranteed and there is only a probability of its occurrence. Each individual’s attitude to probability, sometimes called risk proneness or aversion, has been assumed to be static. Behavioral ecological studies, however, suggest such attitudes are dynamically modulated by the context an organism finds itself in; in some cases, it may be optimal to pursue actions with a low probability of success but which are associated with potentially large gains. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
189
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(213 citation statements)
references
References 54 publications
(85 reference statements)
20
189
0
Order By: Relevance
“…A similar region was active when people imagined how much they would like new and unexperienced food items that were nevertheless composed of familiar components (30). The resting fMRI coupling pattern associated with this region resembled that associated with the two perigenual regions reported by Kable and Glimcher (27) and Kolling et al (10,37) (Fig. 2E); however, the comparative weakness of coupling with the amygdala and temporal cortex areas meant that it most closely resembled a swathe of tissue in the macaque that extended from the anterior cingulate sulcus through area 9 on the dorsal convexity to the principal sulcus.…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations
“…A similar region was active when people imagined how much they would like new and unexperienced food items that were nevertheless composed of familiar components (30). The resting fMRI coupling pattern associated with this region resembled that associated with the two perigenual regions reported by Kable and Glimcher (27) and Kolling et al (10,37) (Fig. 2E); however, the comparative weakness of coupling with the amygdala and temporal cortex areas meant that it most closely resembled a swathe of tissue in the macaque that extended from the anterior cingulate sulcus through area 9 on the dorsal convexity to the principal sulcus.…”
Section: Resultssupporting
confidence: 67%
“…10, and in the supplementary information in ref. 37), and found that it was associated with a similar pattern of coupling (SI Appendix, Fig. S1A), although now there was less coupling with medial temporal regions, such as the amygdala and with dorsal and ventrolateral PFC and more coupling with premotor areas, such as the SMA.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…different brain regions having been evolved to drive decision making in these two choice settings (see also Boorman, Rushworth, & Behrens, 2013;Kolling et al, 2014). Specifically, these authors suggest that dorsal anterior cingulate cortex (dACC) and ventromedial prefrontal cortex (vmPFC) may have evolved to play critical and differential roles in foraging versus economic choice, respectively.…”
mentioning
confidence: 99%